Synthesis and Study of Some Newer Analogues ofQuinolin-8-ol as Potent Antimicrobial Agents - Jyoti Sharma; Sabir Hussain; Mohammad Amir (E-Journal of Chemistry)
New series of 4-(substituted phenyl)-5-[(quinolin-8-yloxy) methyl]-4H-1,2,4-triazole-3-thiol (4a-c), N³-(4-substituted phenyl)-5-[(quinolin-8-yloxy) methyl]-4H-1,2,4-triazole-3,4-diamine (5a-c) and N-(4-substituted phenyl)-5-[(quinolin-8-yloxy) methyl]-1,3,4-thiadiazol-2-amine (6a-g) have been synthesized and the structures of the new compounds were established on the basis of IR, 1H NMR spectral data. In vitro antimicrobial activity (MIC activity) was evaluated and compared with standard drugs of loxacin and ketoconazole. Compounds 5a and 6e in the series have shown interesting antibacterial activity against both S. aureus (gram-positive) and E. coli (gram-negative) organisms. In this paper, we also describe studies leading to identification of antifungal agents. In the gratifying result, most of the compounds were found to have moderate antimicrobial activity.